Efeito citotóxico de agentes clareadores a base de peróxido de hidrogênio a 20% e 38% sobre células odontoblastóides - Sacono, Nancy Tomoko [UNESP]; Coldebella, Cármen Regina [UNESP]; Ribeiro, Ana Paula Dias [UNESP]; Soares, Diana Gabriela de Souza [UNESP]; Trindade, Flávia Zardo [UNESP]; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (My University, 2010)
The aim of this in vitro study was to evaluate the trans-enamel and transdentinal cytotoxic effects of two in-office tooth bleaching techniques that employ bleaching gels containing 20% and 38% of H2 O2 on cultured odontoblast-like cell line (MDPC-23). Sixty enamel/dentin discs were obtained from bovine central incisors and placed individually in artificial pulp chambers. Six groups were formed according to the following enamel treatments: G1- 20% H2 O2 (1 application); G2- 20% H2 O2 (2 applications); G3- 38% H2 O2 (1 application); G4- 38% H2 O2 (2 applications); G5- 38% H2 O2 (3 applications); and G6- control (no treatment). In G1 and G2, the bleaching gel was left in contact with the enamel surface for 45 min in each application. However, in G3, G4, and G5 the bleaching gel was applied for only 10 min per application. After the last application, the extracts were collected and applied on previously cultured cells (30.000 cells/cm2 ) for 24 h. Cell metabolism was evaluated by the MTT assay and cell morphology was analysed by scanning electron microscopy. Cell metabolism decreased by 96.29%; 96.11%; 96.42%; 95.62%; and 97.18% in G1, G2, G3, G4, and G5, respectively. All treated groups differed significantly from non-treated control group (G6) (p < 0.05). However, the difference in cell metabolism among treated groups was not significant statistically. In addition, significant morphological cell alterations were observed in all treated groups. Under the tested experimental conditions, the extracts collected after both tooth bleaching techniques evaluated in this study caused severe toxic effects on cultured odontoblast-like cell MDPC-23.

O objetivo deste estudo foi avaliar a citotoxicidade de diferentes técnicas de clareamento dentário, utilizando agentes clareadores com 20% e 38% de peróxido de hidrogênio (H2O2) sobre células odontoblastóides MDPC-23. Sessenta discos de esmalte/dentina foram adaptados em câmaras pulpares artificiais e divididos em seis grupos de acordo com o tratamento realizado sobre a superfície do esmalte: G1- 20% H2O2 (1 aplicação); G2- 20% H2O2 (2 aplicações); G3- 38% H2O2 (1 aplicação); G4- 38% H2O2 (2 aplicações); G5- 38% H2O2 (3 aplicações) e G6- controle. Em cada aplicação, os agentes clareadores com 20% ou 38% de H2O2 permaneceram sobre o esmalte por 45 ou 10 minutos, respectivamente. Após a última aplicação do gel, o meio de cultura em contato com a dentina foi obtido (extrato) e aplicado sobre as células previamente cultivadas (30.000 células/cm2). Foram realizadas avaliações do metabolismo (Teste de MTT) e da morfologia celular (MEV). A redução do metabolismo celular foi de 96,29%; 96,11%; 96,42%; 95,62% e 97,18% para G1, G2, G3, G4 e G5, respectivamente. Houve diferença estatisticamente significante apenas quando se comparou os grupos tratados com o grupo controle (G6) (Mann Whitney, p<0,05). Nestes grupos tratados, as poucas células que sobreviveram aos extratos apresentavam notáveis alterações morfológicas. Concluiu-se que ambas as técnicas de clareamento avaliadas resultaram em intenso efeito citotóxico trans-amelodentinário para as células MDPC-23.
Cytotoxic effect of a 20% and a 38% hydrogen peroxide bleaching agents on odontoblast-like cells
Keywords: Tooth bleaching; Hydrogen peroxide; Odontoblasts; Clareamento de dente; Peróxido de hidrogênio; Odontoblastos